Epidemiological and Clinical Features of Critical and Non-Critical Elderly COVID-19 Patients in Udayana University Academic Hospital: A Retrospective Study - Purnamasidhi, Cokorda Agung Wahyu; Somia, I Ketut Agus; Junior, Darren; Suteja, Richard Christian; Adiputra, I Komang Hotra; Purnama, Giovanca Verentzia; Weisnawa, I Gede Purna; Jerry; Wulandari, Putu Kintan; Shanti, Dewa Ayu Fony Prema; Diksha, I Gusti Ngurah Ariestha Satya (Indonesian Journal of Tropical and Infectious Disease, 2023)
Elderly COVID-19 patients have been associated with worse outcomes and have been presented with the highest mortality rate. However, studies on the clinical features and the differences between critical and non-critical elderly COVID-19 patients in Indonesia and even other countries are still lacking and rare. In this retrospective study, the epidemiological and clinical features of critical and non-critical elderly COVID-19 patients admitted to Udayana University Academic Hospital between April 2020 and March 2021 were analyzed and then compared. Of the 280 medical records analyzed, 60.7% were male and the median age was 65.0 years old. Based on the medical records, 18.2% of elderly patients met our criteria of critical patients. The most common symptoms presented in both category upon admission included fever and coughing. The most common comorbidity found in critical patients was heart disease and hypertension in non-critical patients. Laboratory results differences included leukocytes, neutrophils, lymphocytes, Neutrophil-to-Lymphocyte Ratio, platelets, SGOT, SGPT, and urea. Only 9.9% of critical patients and 6.1% of non-critical patients were given antiviral therapy. In contrast, 68.6% of critical patients and 76% of non-critical patients were given antibiotics. The mortality rate in critical patients was 70.6% and 0.4% in non-critical patients. Based on the results, a multimodal approach in the treatment of elderly COVID-19 patients is very essential. The higher mortality rate in elderly patients should be able to be reduced by giving early and timely antiviral therapy with the addition of effective choice of drugs.